Pengaruh Electronic Word Of Mouth Terhadap Keputusan Pembelian Minuman Kopi - Yoga Prasetyo; Weny; Tasik Utama (Forum Kerjasama Pendidikan Tinggi, 2024)
Electronic Word of Mouth (e-WOM) has a very influential or effective role in the survival of an industry. Because word of mouth can spread widely quickly and is trusted by potential consumers. Spreading word of mouth can not only be done by conveying information through word of mouth communication, but can also be disseminated via existing internet social media. The aim of this research is to find out whether Electronic Word of Mouth influences purchasing decisions at Fortunate Coffee Medan. While the method used in this research is an associative quantitative method, the data collection method used by researchers is a questionnaire. In this study the population was approximately 500 in the last 2 months, therefore the sample obtained was 84 respondents using the Slovin formula. From the results of the normality test, it is known that the significance value is 0.049 > 0.05, so it can be concluded that the residual value is not normally distributed. Based on the results of the coefficient of determination test, it was found that the E-WOM variable influenced the purchasing decision variable by 44.9%, while the remaining 55.1% showed that the purchasing decision variable was influenced by other variables. Based on the results of the F test, it was found that the fcount value for variable So it can be concluded that H0 is rejected and Ha is accepted, meaning that the E-WOM variable has a significant influence on purchasing decisions at Fortunate Coffee Medan.